The Financial Value of Financial Position in Range the Technical Concept for Civil Right - Mizher, Haider Ali; Alabid, Sadkhan Madhloom Bahedh (Journal of Ecohumanism, 2024)
Background and Objectives : The obligation in civil law is of a financial nature, whether it is linked to the subject matter on which the real rights are based or the personal right, which is debt, and the idea of the exchange value of the financial position is an idea that addresses the actual situations in which financial values (compensations) are realized or cases of use that have, in actual practical terms, a financial value and thus Researching their forms is important from a practical point of view, as it requires studying those forms and their relationship to the technical concept of the financial right, distinguishing things from their subjects and from the rights subject to financial evaluation, and explaining the elements of considering valuable assets in the civil concept.The study aims to achieve the following: Financial position1- Develop a theory of financial positions within the actual scope of use and the actual holdings of the business and the funds. 2- Determine the course of compensation for things and the transfer of the financial position from one description to another according to the patterns of actual purposes and needs. 3- Providing a legal framework that distinguishes between describing a crime related to money and achieving a financial position as a result of the possession of that money.